Validating A Prophetic-Based Assessment Model for Teacher Personality Competence - Atim Rinawati; Siti Fatimah (AL-ISHLAH: Jurnal Pendidikan, 2025)
There is a growing need for valid assessment tools to evaluate teacher personality, particularly those grounded in moral and religious values. This study aims to develop and validate a personality assessment instrument for teachers based on a prophetic approach, which integrates Islamic ethical and spiritual principles. This research followed the ten-stage instrument development framework proposed by Crocker and Algina. A mixed-methods validation design was employed, including expert judgment and Confirmatory Factor Analysis (CFA) using AMOS software. The instrument was tested on three distinct respondent groups to ensure robustness. Expert evaluations confirmed the content validity and feasibility of the developed instrument. CFA results supported a four-dimensional model of teacher personality: transcendent, communicative, commitment, and humanist. Initial CFA results did not meet model fit criteria, necessitating post hoc modifications. The revised model demonstrated acceptable fit indices: RMSEA = 0.077, GFI = 0.934, AGFI = 0.898, TLI = 0.925, and NFI = 0.938. These values indicate the instrument possesses strong construct validity and reliability. The validated instrument effectively captures key dimensions of teacher personality aligned with prophetic values and can be applied in Islamic educational contexts. Its development addresses a critical gap in teacher assessment tools by incorporating moral and spiritual foundations. Future research may explore its application across broader educational settings.